Strategi Pembelajaran - Gep Rianto; Reza Hanafi; Gusmanelli Gusmanelli (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The purpose of this study was to determine the basic learning strategies that can be used to increase students' knowledge. This research uses literature review method. Learning strategies are very useful for teachers and students in the learning process. For teachers, this learning strategy is used as a new and systematic regulatory reference in the implementation of learning. For students the use of learning strategies can facilitate the learning process and understand the content of learning, because each learning strategy is designed to facilitate the learning process. It is hoped that this learning strategy can improve student learning outcomes.